ANALISIS PENGARUH KUALITAS PELAYANAN JASA TERHADAP KEPUASAN KONSUMEN PADA LEMBAGA PENDIDIKAN PROFESIONAL (LPP) MASTER KOMPUTER CABANG METRO TAHUN AKADEMIK 2011/2012 - Ria Resti Bekti Utami; I Komang Winatha; Tedi Rusman (FKIP Unila, 2013)
the purpose of this research is to know the factors that affect customers’ satisfaction ofBranch LPP Master KomputerMetro in academic year 2011/2012 are limited to the tangible variables (physical evidence), empathy (caring), reliability (reliability), responsiveness (quick response), and the assurance (collateral). This research used descriptive verification design with ex post factor and survey approach.The population in this researchwere all students who attendedcomputer tutorial on Branch of LPP Master Computer Metro in Academic Year 2011/2012 with amount of students’ is 95. This study was a study population because the sample used the entire population or a sample saturated. Data collection techniques in this study were observation, interviews, and questionnaires. The hypothesesanalyzed used simple linear regression and multiple linear regressions. Based on the analysis of the data obtained the following results: 1. There was influence of tangible for customers’ satisfaction of BranchLPP Master Komputer Metro in academic year 2011/2012 were shown by a simple linear regression test results obtained r ² = 0.140. 2. There was influence of empathy (caring) toward customers’ satisfaction of BranchLPP Master KomputerMetro in academic year 2011/2012 were shown by a simple linear regression test results obtained r ² = 0.117. 3. There was influence of reliability (reliability) toward customers’ satisfaction of BranchLPP Master KomputerMetro in academic year 2011/2012 were shown by a simple linear regression test results obtained r ² = 0.126. 4. There was influence responsiveness (responsiveness) towardcustemers’ satisfaction of BranchLPP Master Komputer Metro in academic year 2011/2012 were shown by a simple linear regression test results obtained r ² = 0.260. 5. There was the influence of assurance (security) toward customers’ satisfaction of BranchLPP Master Komputer Metro in academic year 2011/2012 were shown by a simple linear regression test results obtained r ² = 0.157. 6. There were influences quality of service toward customers’ satisfaction of BranchLPP Master KomputerMetro in academic year 2011/2012 were shown by the results obtained by multiple linear regression R ² = 0.515. Keywords: customer satisfaction